Menggagas Fiqh Realita Dalam Kehidupan Keagamaan di Indonesia - Abdurrahman Kasdi (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
This article aims to describe the significant of the sociological approach to formulate the fiqh (Islamic jurisprudence) of reality within the religious life of the Indonesian society. The study of reality is needed in the social and religious sciences, especially in the fiqh studies because it is capable to be a natural activator of the transformation in formulating the Indonesian fiqh. The research approach used is a sociological approach. The results show that the fiqh of reality is a part of the Islamic jurisprudence that has relevance to the reality of society. In applying of this fiqh, there are needs to be an effort to contextualize of interpreting the text so that the understanding of it is not literally according to the sound of the text. In this context, the reality consists of two forms, namely: a fixed and changing reality. The fixed reality is the nature (sunnah) of Allah in this universe which has been pointed out in the Qur'an that this reality will not shift. The changing reality can be seen from the general and partial reality. The general reality is a different human tradition because of difference in the place and time, while the partial one is just for certain individual condition. The implementation of the such fiqh is necessary for the Indonesian Muslims, especially in building the harmonization of the national life.